A proteomic approach towards understanding the pathogenesis of Mooren's ulcer. (April 2021) - Chi, Hao; Hao, Wenpei; Qi, Xia; Zhang, Ting; Dong, Yanling; Gao, Hua; Wei, Chao; Shi, Weiyun
Abstract: Mooren's ulcer (MU) is a refractory autoimmune corneal ulcer with a high recurrence rate. So far, its molecular profiles and pathomechanisms remain largely unknown. Therefore, we aim to characterize the protein profiles of MU specimens by data-independent-acquisition (DIA) mass spectrometry (MS), and to define the functions of differentially-expressed proteins (DEPs). Through LC-MS/MS, 550 DEPs were identified between MU biopsies and age-matched controls (Ctrl). KEGG analysis revealed that the significantly enriched pathways of the up-regulated proteins mainly covered lysosomes, antigen processing and presentation, and phagosomes. We subsequently validated the expressions of the selected candidates using parallel-reaction-monitoring (PRM)-based MS and immunohistochemistry (IHC), including cathepsins, TIMP3, MMP-10, MYOC, PIGR, CD74, CAT, SOD2, and SOD3. Moreover, immunoglobulin (Ig) components and B lymphocytes associated proteins MZB1, HSPA5, and LAP3 in MU were significantly increased and validated by PRM-based MS and IHC. The remarkable enrichment of neutrophil extracellular traps (NETs) components in MU samples was also identified and determined. The up-regulated Ig components and NETs components suggested that B lymphocytes and neutrophils participated in the immunopathology of MU. Importantly, we also identified and validated much more expression of peptidyl arginine deiminase 4 (PADI4) in MU samples. The double-immunofluorescence staining showed the co-localization of citrulline residues with MPO, NE, and IgG in MU samples. These results indicated the presences of PADI4-mediated citrullination modification and anti-citrullinated protein antibodies (ACPAs) in MU samples. Our findings, for the first time, provide a global proteomic signature of MU, which may open a new avenue towards disease pathology and therapeutics. Highlights: We for the first time provide a global protein profile of MU through a proteomic approach. Our finding highlight the critical contributions of B lymphocytes and neutrophils to MU immunopathogenesis. PADI4-mediated citrullination modification probably involved in the pathogenesis of MU.